Prawo międzynarodowe a uniwersalność pojęcia systemu - Stępień, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The key feature of international law is that states are primary subjects of this law. This results in other features of international law like high relevance of customary law, ambiguous meaning of the term “treaty”, considerable role of soft law, uncertainty about the effects of reservations to treaties, and above all, the lack of collision rules when two or more treaties bind partly different parties. This all supports the weaker thesis about systemness of international law. The weaker thesis about systemness of international law is not the answer to all questions that can be put in this respect. This is particularly evident in the case of consistency of international law which is seriously jeopardized by the progressive fragmentation. But the conviction of the systemness of international law has also somewhat different purpose than it seems. Namely, it strengthens the argument that international law is the law in the proper sense of the word. It fulfils therefore, to some extent, a persuasive function. International law confronted with domestic law is a kind of so-called “positive morality” for many lawyers. Therefore, the thesis about systemness of international law is so important. For similar reasons, H. Kelsen so firmly stressed that war is a sanction, what justified the view that international law is the law in the proper sense of the word.
Keywords: prawo międzynarodowe; dogmatyka prawa międzynarodowego; dogmatyka prawa